PENINGKATAN HASIL BELAJAR KETERAMPILAN PASSING ATAS PERMAIANAN BOLA BESAR MELALUI MODIFIKASI ALAT PADA KELAS V SEKOLAH DASAR NEGERI SUNGAI BAHALANG - Robi Susman (Lambung Mangkurat University, 2014)
Improved Learning Results Skills Passing Top Game Ball Large Through Modification Tool On Class V State Of Elementary School Sungai Bahalang. Purpose of this research is to improve the skills of passing over onthe great ball game by modifying tools.The research was carried out in state of elementary school Sungai Bahalang District Tapin Tengah Regency Tapin on Wednesday 26 February 2014, Wed 05 March 2014 and Wednesday 12 March 2014.Subyek research is peserta student class V in state of elementary school Sungai Bahalang District Tapin Tengah Regency Tapin 2013/2014 totalling7 people composed of3learners ' son, and4learners daughter.Methods used in penelitianThis is a class action Research that done in two cycles of three meetings.Results of the study revealed that, from the cycle I and cycle II is seen in every meeting there is increasing study results from previous meetings.From preliminary datashows the average value of the learners is 54,46 and all learners no one completely.After themeeting I cycle 1 an increase in the average value of 66,43 and persentaseketuntasan learners are people who 2% (28,57 completely). At its meeting of 2 cycle I average value increased to71,01 and ketuntasan as well as percentage increases to 71,43%. On cycle II meetings 1 average value has reached 80,36 (Midday) and pesentaseketuntasan was 100%. This indicates that tindakan given by researchers that is pembelajaran through modification of the tool provide a positive impact to learning outcomes learner. The existence of positive impact of improved learning outcomes learner, then it can be said to be Penelitian this Class Action is successful.Based on the results of this study, subjects to the teacher of physical education and health to be Amore creative and professional so that it can make learners actively moving in following learning, one of trick is to use modified toolsso learning objectives can be achieved. Keyword: improved, learning results, skills passing, modification tools